(untitled) (Legal journal - Research in Legal and Social Sciences, 2018)
The most accurate definition for human trafficking is “the 21st Century version of slavery”. This felony was known and approached, at the beginning, as a problem of prostitution, of a reather moral than legal nature. Over centuries, this felony offense was not important for criminal law, until the moment when paradigms change, with the influence of human rights, and the intervention of the State becomes transversal. The present research developes the highlights of the criminal classification of human trafficking in Paraguay, its complexity as a part of organized crime and the universal definition of this felony offense - which is essential when prosecuting it- and its constrast to Spanish law, as well as the international legal alignment, achieved due to the Palermo Protocol.